Analysis of mtDNA control region of an isolated population of Eld's deer (Rucervus eldii) reveals its vulnerability to inbreeding. Issue 1 (1st January 2017) - Angom, Sangeeta; Kumar, Ajit; Gupta, Sandeep Kumar; Hussain, Syed Ainul
Abstract: The Eld's deer or brow-antlered deer ( Rucervus eldii ) is one of the most endangered cervids of Southeast Asia. Geographically, it has three distinct subspecies; Sangai or Manipur's brow-antlered deer ( R. e. eldii ), Siamese brow-antlered deer ( R. e. siamensis ) and Thamin or Myanmar's brow antlered deer ( R. e. thamin ). We examined the genetic diversity of wild and captive populations of R. e. eldii and compared its relationship with other subspecies using mtDNA control region gene. During the analysis, only one haplotype was detected in 30 samples of R. e. eldii. No genetic variation was observed among the R. e. eldii populations. The reduced genetic diversity indicates that the population has passed through the bottleneck effect that might have resulted in the inbreeding depression.